The Enterotoxin Gene Profiles and Enterotoxin Production of Staphylococcus aureus Strains Isolated from Artisanal Cheeses in Belgium - Raphaëlle Minutillo; Barbara Pirard; Abdelhak Fatihi; Marina Cavaiuolo; Donatien Lefebvre; Amaury Gérard; Bernard Taminiau; Yacine Nia; Jacques-Antoine Hennekinne; Georges Daube; Antoine Clinquart (Foods, 2023)
A Staphyloccoccus aureus is one of the leading causes of food poisoning outbreaks (FPOs) worldwide. Staphylococcal food poisoning (SFP) is induced by the ingestion of food containing sufficient levels of staphylococcal enterotoxins (SEs). Currently, 33 SEs and SE-like toxins (SEls) have been described in the literature, but only five named “classical” enterotoxins are commonly investigated in FPOs due to lack of specific routine analytical techniques. The aims of this study were to (i) establish the genetic profile of strains in a variety of artisanal cheeses (n = 30) in Belgium, (ii) analyze the expression of the SE(l)s by these strains and (iii) compare the output derived from the different analytical tools. Forty-nine isolates of S. aureus were isolated from ten Belgian artisanal cheeses and were analyzed via microbiological, immunological, liquid chromatography mass spectrometry, molecular typing and genetic methods. The results indicated that classical SEs were not the dominant SEs in the Belgian artisanal cheeses that were analyzed in this study, and that all S. aureus isolates harbored at least one gene encoding a new SE(l). Among the new SE(l)s genes found, some of them code for enterotoxins with demonstrated emetic activity and ecg-enterotoxins. It is worth noting that the involvement of some of these new SEs has been demonstrated in SFP outbreaks. Thus, this study highlighted the importance of the development of specific techniques for the proper investigation of SFP outbreaks.